Unveiling the Impact of Enhanced Recovery After Surgery Programs on Post-Operative Morbidity and Mortality: Enhanced Recovery After Surgery Programs on Post-Operative Morbidity - Sami, Asad; Rafiq, Kashif; Ahmed, Zahoor; Khan, Muhammad Umer Farooq; Noor, Danish; Khan, Muhammad Usama (Pakistan Journal of Health Sciences, 2024)
Enhanced recovery after surgery is an evidence-based and holistic perioperative care approach and a real revolution in surgical settings. Initially, this concept referred to as “fast-track surgery’’ has evolved to enhanced recovery after surgery and acquired remarkable attention for its potential to improve patient recovery and surgical adverse outcomes, reduce the length of hospital stay, and yield beneficial impact on post-surgical mortality and morbidity. Objective: To evaluate the impact of enhanced recovery after surgery programs on Post-Operative Morbidity and Mortality. Methods: A comprehensive overview was provided based on several studies’ data on the impact of enhanced recovery after surgery programs on postoperative mortality and morbidity. Nine years of epidemiological studies published between 2014-2023 were included based on the presence of qualitative and quantitative data. Results: Enhanced recovery after surgery significantly reduces the overall morbidity, surgical site infections, and complications associated with different surgeries, and shortens the length of stay at the hospital without escalating the readmission and mortality rate. However, only one study reported a significant difference in mortality rate between enhanced recovery after surgery and the control group. Conclusions: It was concluded that enhanced recovery after surgery protocols have increasingly been recognized as pivotal tools in reducing postsurgical mortality and morbidity, highlighting their efficacy in optimizing surgical consequences. By synthesizing core insights this review emphasizes the concrete advantage of enhanced recovery after surgery programs inpatient rehabilitation mobilization, encompassing faster recovery, and reducing surgical-related adverse effects.